Use of labeled histology images with key identification for histology teaching learning - K Sujatha (Wolters Kluwer Medknow Publications, 2020)
Background and Objectives: Histology learning conceptualizes the photographic memory of the observed section, which is not only tedious but also confusing in nature. The main objective of the present study was to evaluate the effectiveness of labeled histology images, with key identification points shared on WhatsApp (or other social media) during the identification process of histology slides among first year medical undergraduates. Methodology: In a quasi-experimental study involving medical first year undergraduate students of two medical colleges from south India, from October 2018 to May 2019, the learning outcomes were evaluated. A total of 242 students participated in the study. Group A received labeled histology images with key identification points through WhatsApp (or other social media or by a blog post) 2 days after the routine test. It was followed by a surprise test for the whole batch. Group B students received labeled images after the surprise test. Two weeks later, a revision test was conducted. Learning outcomes of spotter test scores were compared with Student t-test. Results: Students of group A have scored significantly more marks in the surprise test in both colleges compared with group B. The results indicate that groups that have been exposed to the labeled images with key identification points resulted in significant improvement in the scores in histology slide identification. Conclusion: Use of labeled images with key identification points and sharing with students improves histology-learning outcomes.